Pengaruh Proporsi Odeng Ikan Kembung, Nangka Muda, dan Penambahan Ekstrak Kayu Secang Sebagai Pewarna Terhadap Daya Terima Kudapan Sumber Omega-3 dan Serat Untuk Mencegah Penyakit Kardiovaskular - Hidayatush Shoimah, Lutfi; Ismawati, Rita (Medic Nutricia : Jurnal Ilmu Kesehatan, 2025)
Background: The emergence of foreign cuisines in Indonesia, which are available in modern and traditional markets, presents promising business opportunities, exemplified by odeng (oden). Odeng is a processed product made from mackerel fish, produced through frying. However, frequent frying methods can contribute to cardiovascular diseases. Preventive measures have been taken by utilizing inexpensive mackerel fish high in omega-3 fatty acids, as it can reduce triglyceride levels. Young jackfruit, which is high in fiber, and sappan wood extract, used as a natural coloring agent, can enhance the appeal of odeng. Objectives: This study aims to determine the effect of the proportions of mackerel fish, young jackfruit, and sappan wood extract on acceptability, omega-3 content, fiber content, and selling price determination. Methods: An experimental research method was used with five treatments, and a hedonic test was conducted with 33 untrained panelists. The proportions of mackerel fish and young jackfruit were F1 (30%:70%), F2 (40%:60%), F3 (50%:50%), F4 (60%:40%), and F5 (70%:30%), with 10 ml of sappan wood extract added to each formula. Data analysis used the Kruskal Wallis test with the Mann-Whitney follow-up test. Results: Proportions of mackerel fish, young jackfruit and sappan wood extract odeng significantly affected consumer acceptance, with Formula F4 identified as the best, containing 0.84 g of omega-3 and 0.48 g of fiber, and could be marketed at IDR 6,000. Conclusions: The best formula of odeng that F4 showcase favorable sensory attributes, offer an affordable price, and omega-3 requirement, although the fiber content was not sufficient to qualify as a fiber source.